Backbiting and Its Consequences on The Psychological Dimensions of The Perpetrator: An Analysis from The Perspectives of The Qur’an and Hadith - Soewandi Putri, Halimah (DAYAH: Journal of Islamic Education, 2025)
This study aims to examine the psychological impacts of backbiting (ghibah) on the various dimensions of the human psyche from the perspectives of the Qur’an and Hadith. The research employs a qualitative method using a library research approach by analyzing relevant Qur’anic verses, Prophetic traditions, and scholarly literature related to Islamic psychology. The findings indicate that backbiting exerts destructive effects on five major dimensions of the human psychological structure: an-nafs (the self), al-‘aql (intellect), al-qalb (heart), ar-rūḥ (spirit), and fiṭrah (innate human disposition). Psychologically, engaging in gossip may trigger stress, anxiety, feelings of guilt, envy, and emotional instability, which can disrupt an individual’s mental and spiritual balance From the Qur’anic perspective, this behavior is likened to consuming the flesh of one’s deceased brother (Qur’an 49:12), while the Hadith categorizes it as a grave sin capable of eroding the rewards of good deeds. This study highlights that controlling one’s speech is not merely a moral obligation in Islam but also functions as a psychological and spiritual mechanism for maintaining inner balance and achieving spiritual tranquility (as-sakīnah).